2013
DOI: 10.1074/jbc.m113.471466
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-inducible Factor-1α (HIF-1α) Promotes Cap-dependent Translation of Selective mRNAs through Up-regulating Initiation Factor eIF4E1 in Breast Cancer Cells under Hypoxia Conditions

Abstract: Background: Hypoxia promotes tumor growth, but connections to translation mechanisms are obscure. Results: Hypoxia-enhanced tumorsphere growth of breast cancer cells is HIF-1␣-dependent, and HIF-1␣ up-regulates eIF4E1 in hypoxic cancer cells. Conclusion: HIF-1␣ promotes cap-dependent translation of selective mRNAs through up-regulating eIF4E1 in cancer cells at hypoxia. Significance: Our study provides new insights into the translation mechanisms in cancer cells under low O 2 concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 62 publications
4
56
1
Order By: Relevance
“…PDGFRA has also been linked to aggressive colorectal carcinomas (35). We did not observe noticeable differences in eIF4E protein levels across all five cell lines; however, 3-fold increases in eIF4E in a HIF1␣-dependent manner in a hypoxic breast cancer cell line suggest that cancerspecific mutation profiles may have different effects on the regulation of cap-dependent translation (36).…”
Section: Discussionmentioning
confidence: 51%
“…PDGFRA has also been linked to aggressive colorectal carcinomas (35). We did not observe noticeable differences in eIF4E protein levels across all five cell lines; however, 3-fold increases in eIF4E in a HIF1␣-dependent manner in a hypoxic breast cancer cell line suggest that cancerspecific mutation profiles may have different effects on the regulation of cap-dependent translation (36).…”
Section: Discussionmentioning
confidence: 51%
“…5A). Previously, we reported that 4EGI-1 inhibits translation of several oncogene mRNAs without affecting their transcription in multiple cancer cell lines at 24hr under normoxia and at 12hr under hypoxia conditions in vitro [16, 32]. These observations suggested that the indicated decreased protein levels in 4EGI-1 treated BCSC tumors were primarily, if not all, caused by selective inhibition of translation of mRNAs encoding these proteins.…”
Section: Resultsmentioning
confidence: 89%
“…eIF4E is overexpressed in a variety of cancers and is a target of modern therapies (36)(37)(38)(39)(40)(41). Furthermore, eIF4E contributes to tumorsphere growth in hypoxic breast cancer cells (42). Indeed, eIF4E remains an attractive target to inhibit the growth of cancer cells.…”
Section: Discussionmentioning
confidence: 99%